The Implications of Bone Marrow Adipose Tissue on Inflammaging - Aaron, Nicole; Costa, Samantha; Rosen, Clifford J.; Qiang, Li (Frontiers in Endocrinology, 2022)
Once considered an inert filler of the bone cavity, bone marrow adipose tissue (BMAT) is now regarded as a metabolically active organ that plays versatile roles in endocrine function, hematopoiesis, bone homeostasis and metabolism, and, potentially, energy conservation. While the regulation of BMAT is inadequately understood, it is recognized as a unique and dynamic fat depot that is distinct from peripheral fat. As we age, bone marrow adipocytes (BMAds) accumulate throughout the bone marrow (BM) milieu to influence the microenvironment. This process is conceivably signaled by the secretion of adipocyte-derived factors including pro-inflammatory cytokines and adipokines. Adipokines participate in the development of a chronic state of low-grade systemic inflammation (inflammaging), which trigger changes in the immune system that are characterized by declining fidelity and efficiency and cause an imbalance between pro-inflammatory and anti-inflammatory networks. In this review, we discuss the local effects of BMAT on bone homeostasis and the hematopoietic niche, age-related inflammatory changes associated with BMAT accrual, and the downstream effect on endocrine function, energy expenditure, and metabolism. Furthermore, we address therapeutic strategies to prevent BMAT accumulation and associated dysfunction during aging. In sum, BMAT is emerging as a critical player in aging and its explicit characterization still requires further research.